Manajemen Kesiswaan Berbasis Pesantren Dalam Pembentukan Karakter Siswa di MTs Darul Huda - Kholifatus Solikah; Muhamad Thoyib (Excelencia: Journal of Islamic Education & Management, 2025)
At this time, various social layers have been affected by the moral crisis. What is more worrying is that this moral crisis has spread to the world of education, especially the students themselves. MTs Darul Huda offers a solution by applying student management concepts that are in accordance with scientific management functions, also based on instilling moral values. This research aims to determine the planning, development and impact of Islamic boarding school-based student affairs in the formation of student character at MTs Darul Huda. This research uses a qualitative approach with a case study type of research. The results of this research are (1) Planning for Islamic boarding school-based student management in the formation of student character has been carried out since the beginning of MTs Darul Huda and has been developed to suit current developments and issued several policies including: Additions to the curriculum system (adabuna and ubudiyah), all students are required to attending the MMH school, as well as the formation of student character in accordance with Islamic boarding school values. (2) Islamic boarding school-based student development in the formation of student character at MTs Darul Huda through three strategies, namely moral knowing, moral feeling and moral action and implemented in the form of students' academic and non-academic activities. (3) Islamic boarding school-based student management in the formation of student character received a positive response and had a positive impact as well as seeing an increase in student learning outcomes and achievements as well as students' daily behavior.